PENGARUH TAPAK PADA GEDUNG KESENIAN BALIKPAPAN - Atik Adinda; Sefriyandri Sefriyandri; Fitri Silfani Angraini; Maya Agustini (Jurnal Arsitektur Display, 2022)
The city of Balikpapan has a multipurpose building infrastructure that is intended to provide facilities for the community to hold art activities. The building is called the Balikpapan Arts Building. The activities of a multipurpose building must match the activities of the building. This study aims to determine how much influence the site has on the design of the Balikpapan Arts Building and its sustainability impact. This study uses a qualitative research paradigm using architectural site analysis tools with circulation, topography, zoning, visual, zoning, climate and regulatory aspects approaches. This study concludes that the influence of the site is very crucial to the shape of the design of the Balikpapan Arts Building, the aspects with the highest influence on the site of the Balikpapan Arts Building are visual, topographical and circulation aspects, while aspects that have a weak influence are regulation, climate and zoning.